Pseudoxanthoma elasticum with prominent arterial calcifications evoking CD73 deficiency. (October 2019) - Devriese, Magali; Legrand, Anne; Courtois, Marie-Cécile; Jeunemaitre, Xavier; Albuisson, Juliette
Pseudoxanthoma elasticum (PXE) is a rare disorder characterized by skin, eye, and cardiovascular lesions due to ectopic mineralization and fragmentation of elastic fibers of connective tissues. We present an atypical case of PXE with diffuse vascular calcification and negligible skin and eye lesions. The patient was a 37-year-old man suffering from severe bilateral arterial calcifications in superficial femoral and posterior tibial arteries. Eye fundoscopy and skin examination were first considered normal. This phenotype suggested first the diagnosis of Arterial Calcification due to Deficiency of CD73 (ACDC) characterized by mutations in NT5E gene. However, we found two variants in ABCC6 gene, and no variant in NT5E. Skin reexamination revealed few lateral skin papules confined to the scalp. Phenotypic overlap was described in vascular calcification disorders, between GACI and PXE phenotypes, and we discuss here expansion of this overlap, including ACDC phenotype. Identification of these expanding and overlapping phenotypes was enabled by genetic screening of the corresponding genes, in a systematic approach. We propose to create a calcification next generation sequencing (NGS) panel with NT5E, GGCX, ENPP1, and ABCC6 genes to improve the molecular diagnosis of vascular calcification.